DISSEMINATION OF THE USE OF TEXT-TO-SPEECH APPLICATIONS TO DEVELOP LISTENING MATERIAL BASED ON LOCAL WISDOM: DISEMINASI PENGGUNAAN APLIKASI TEXT-TO-SPEECH UNTUK PENGEMBANGAN MATERI AJAR LISTENING BERBASIS KEARIFAN LOKAL - Indasari, Nur Laili; Rosyidi, Ali; Zulfa, Athena (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: Preliminary studies reveal a notable challenge for English teachers: the difficulty in creating learning materials that effectively meet students' needs. In response, researchers have developed innovative listening materials rooted in the local wisdom and religious values of Gresik, utilizing advanced text-to-speech applications. Objective: This initiative aims to empower English teachers in Gresik by sharing research findings related to these materials. Our goal is to enable teachers to implement these resources in their classrooms and inspire them to create their own engaging learning materials using text-to-speech technology. Method: We engaged with four Madrasah Aliyah schools through socialization techniques, concluding with a feedback questionnaire. Results: The feedback was overwhelmingly positive, with 95.2% of teachers affirming that the materials aligned with their educational needs. Participants demonstrated significant skill development, transitioning from a lack of knowledge about the application to feeling motivated to create their own resources. Conclusion: This initiative not only enhances teachers’ technical skills but also nurtures their soft skills. By embracing innovative teaching methods, educators are encouraged to tailor learning materials to meet the diverse needs of their students while leveraging Artificial Intelligence to enrich the educational experience.